Academic achievements and homeschooling—It all depends on the goals. (December 2016) - Neuman, Ari; Guterman, Oz
Highlights: Academic achievement is used to compare homeschooling and school going children. This is sometimes misguided. Structured homeschooling share goals with schools. Unstructured homeschooling might have different educational goals. Therefore has to be evaluated differently. Abstract: This article discusses assessment of academic achievement in the context of home schooling or elective home education (EHE). It presents the argument that although academic achievement is used to compare between homeschooling and school learning, in many cases this comparison is misguided. The achievements of homeschooled children have been examined extensively, but the questions to be considered is whether or not the evaluation methods used were suited to the teaching and education taking place in the homeschooling context, and in particular whether these evaluation methods are compatible with the educational objectives of this framework. This question is fundamental to understanding the homeschooling phenomenon and also to the attempt to compare the achievements of students studying in schools with those of students learning in a homeschooling environment. The article opens with a brief description of the homeschooling phenomenon, introduces a short review of studies comparing academic achievement in this context, presents a number of basic concepts in the field of evaluation as well as an evaluation model relevant to the questions that form the basis of this study, and examines whether, and under what conditions, a comparison can be made between children attending school and those studying in the homeschooling framework.